IMPLEMENTASI E-AUCTION DALAM PELAYANAN LELANG NEGARA DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG SEMARANG - Zevin Muzakki Gumay; Wijayanto Wijayanto (Journal of Politic and Government Studies, 2026)
E-Auction is a web-based electronic auction system implemented by the State Assets and Auction Service Office (KPKNL) Semarang as part of the e-government transformation in public service delivery. Based on preliminary observations, the implementation still faces various challenges related to technological infrastructure, digital literacy, system security, and integration. This study examines how e-auction implementation operates in state auction services at KPKNL Semarang and identifies the obstacles faced as well as efforts undertaken to optimize its implementation. The research employs a descriptive qualitative method with data collected through in-depth interviews, observation, and documentation involving auction functionaries at KPKNL and service users. Data were analyzed using George C. Edwards III’s policy implementation theory — encompassing communication, resources, disposition, and bureaucratic structure — along with the good governance concept focusing on transparency and accountability. The results show that the implementation of e-auction at KPKNL Semarang has proceeded effectively in line with applicable regulations, particularly PMK No. 213/PMK.06/2020. The system has successfully improved efficiency, transparency, and accessibility of state auction services while increasing public participation nationwide. However, challenges remain, including server instability during peak access periods, uneven levels of digital literacy among the public, and the need for broader socialization. These obstacles are being addressed through periodic system improvements, human resource capacity building, and outreach activities. Overall, e-auction has proven to be a significant public service innovation that supports the realization of good governance principles in state auction administration.